2010
DOI: 10.1016/j.cbpb.2009.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant-based feed ingredients on osmoregulation in the Atlantic salmon lens

Abstract: Lenses of adult Atlantic salmon fed with a plant oil and plant protein-based diet (plant diet) were compared to lenses of fish fed a diet based on traditional marine ingredients (marine diet) with respect to biochemical composition and functionality ex vivo. After 12 months of feeding, plant diet-fed fish had smaller lenses with higher water contents and lower concentrations of histidine (His) and N-acetylhistidine (NAH) than fish fed with the marine diet. Cataract development in both dietary groups was minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…It has also been shown that diet composition affects lens His and NAH accumulation rate and synthesis (Tröβe et al . ). However, although dietary requirements have been relatively well defined in diploids (NRC ), no work has to date been conducted in triploids specifically addressing dietary His requirements and correlation with occurrence of cataract.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…It has also been shown that diet composition affects lens His and NAH accumulation rate and synthesis (Tröβe et al . ). However, although dietary requirements have been relatively well defined in diploids (NRC ), no work has to date been conducted in triploids specifically addressing dietary His requirements and correlation with occurrence of cataract.…”
Section: Discussionmentioning
confidence: 97%
“…), although Tröβe et al . () reported that utilization of NAH is more efficient in lens osmoregulation than efflux of other amino acids as a compensatory mechanism in such instances. Ploidy has been reported to affect amino acid levels as demonstrated in tench ( Tinca tinca ) (Buchtova et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In sea bream (Sparus auratus), mRNA levels of osteonectin are low in the liver and other soft tissues in comparison to hard tissues such as scales and bone (Redruello et al, 2005). However, SPARC expression (osteonectin) levels in the lenses of Atlantic salmon are influenced by diet (Tröβe et al, 2010) suggesting the regulation of this gene is linked with metabolism in fish.…”
Section: Discussionmentioning
confidence: 98%